Managing Fiscal Risk in Bulgaria - Brixi, Hana Polackova; Shatalov, Sergei; Zlaoui, Leila (World Bank, Washington, DC, 2015)
To understand the fiscal position of a country, contingent liabilities and other sources of fiscal risk need to be considered. The authors develop a framework to assess and manage fiscal risk in Bulgaria. Bulgaria's Currency Board Arrangement has effectively imposed fiscal discipline, but leaves only limited room to accommodate potential fiscal shocks. Through risks embedded in the portfolio of government contingent and direct liabilities, significant fiscal pressures could arise in the future. Major sources of risk include environmental liabilities and investment requirements, collection capacities of the social protection institutions, and further engagement in off-budget programs, such as government guarantees. To limit the Government's exposure to risks, yet accommodate investment needs crucial to growth and development, Bulgaria must find an optimal strategy for liability management, fiscal reserves, and risk mitigation. Priorities for dealing with existing risks and limiting further accumulation of risks include: 1) Mitigating currency and interest rate risks in the government liability structure. 2) Implementing proposed institutional and finance reform of the country's pension and health care systems. 3) Building adequate contingency reserves. 4) Introducing risk-sharing arrangements. 5) Prioritizing and placing strict limits on the amounts of new guaranteed obligations. 6) Developing government capacity to analyze and manage risks. 7) Fully integrating fiscal risk management with other policy considerations in fiscal management, as part of an integrated asset and liability management strategy.